Analisis Yuridis Terhadap Ketidakpastian Hukum Dalam Cerai Ghaib Di Indonesia - Nilam Permata Sari; Navyra Berlianny; Yuli Andini Puspitasari; Marnia Rani (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Unseen divorce is a phenomenon that reflects the complexity of marital problems in modern times, where communication and physical presence play an important role in the continuity of marital relationships. The case of supernatural divorce shows the need for legal protection and certainty for the bereaved spouse so that they can continue their lives clearly and legally. In the context of marriage, a wife whose husband is declared mafqud faces a legal and moral dilemma regarding her marital status and personal rights. Therefore, Islamic law provides certain guidelines regarding how to handle mafqud cases to ensure justice and legal certainty for all parties involved.